(untitled) (Research, Society and Development, 2022)
Brazil, from the 1990s onwards, with education reforms and the modernization of the State, implemented policies aimed at evaluating and gauging education. In 2005, IDEB was created, which is an index that quantifies students’ learning in Portuguese and Mathematics, relating it to school flow. This study analyzes IDEB’s educational indicators in the state of Amapá and their relationship with the quality of education offered in elementary school in the early years. Through the collection of data on public platforms of educational indicators, low educational indicators were found, which is a reflection of the influence of two factors analyzed in this research: the lack of infrastructure and learning equipment and also the absence of democratic management in almost all of the public schools in Amapa, facts that prevented the state from achieving the IDEB goals between 2013 and 2019.